Management of Gram-Positive Bacterial Disease: Staphylococcus aureus, Streptococcal, Pneumococcal and Enterococcal Infections - Shelburne, Samuel (Principles and Practice of Cancer Infectious Diseases, 2011)
Gram-positive bacteria are a diverse group of organisms that are a major source of morbidity and mortality in patients with cancer. The increasing use of long-term indwelling central catheters and cytotoxic chemotherapies has contributed to the emergence of Gram-positive bacteria as the leading cause of bacteremia in cancer patients. These organisms are also among the foremost causes of pneumonia, skin and soft-tissue infections, osteomyelitis, and central nervous system infections in cancer patients. Gram-positive organisms have a remarkable ability to develop resistance to many of the currently available antimicrobials, but the predilection to become antimicrobial resistant varies substantially for particular organisms and for individual antimicrobial agents. Therefore physicians treating cancer patients need to be familiar with the common clinical manifestations, complications, and treatment options for a wide variety of diseases caused by Gram-positive bacteria.